2010
DOI: 10.1007/s00109-010-0622-5
|View full text |Cite
|
Sign up to set email alerts
|

Sustained expression of NADPH oxidase 4 by p38 MAPK-Akt signaling potentiates radiation-induced differentiation of lung fibroblasts

Abstract: Radiation-induced fibrosis (RIF) is a long-term adverse effect of curative radiotherapy; however, the distinct molecular mechanisms of RIF in neighboring normal tissue are not fully understood. We investigated the mechanisms underlying radiation-induced fibroblast differentiation into myofibroblasts. Lung fibroblasts produced reactive oxygen species (ROS) immediately after irradiation, the level of which remained increased for 24 h. The NADPH oxidase inhibitor, diphenyleneiodonium (DPI), suppressed ROS product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 32 publications
5
31
0
Order By: Relevance
“…O-GlcNAc may influence the expression or function of a variety of proteins involved in high-glucose-induced ROS production. On the other hand, it is equally plausible that much of this effect of OGT shRNA on ROS is secondary to inactivation of p38, which can phosphorylate the NADPH oxidase subunit p47 phox (57) and upregulate the expression of the NADPH oxidase Nox4 (54). Reinforcing this view, the p38 inhibitor SB-203580 has been shown to block high-glucose-induced increases in ROS in mesangial cells (60).…”
Section: Discussionmentioning
confidence: 94%
“…O-GlcNAc may influence the expression or function of a variety of proteins involved in high-glucose-induced ROS production. On the other hand, it is equally plausible that much of this effect of OGT shRNA on ROS is secondary to inactivation of p38, which can phosphorylate the NADPH oxidase subunit p47 phox (57) and upregulate the expression of the NADPH oxidase Nox4 (54). Reinforcing this view, the p38 inhibitor SB-203580 has been shown to block high-glucose-induced increases in ROS in mesangial cells (60).…”
Section: Discussionmentioning
confidence: 94%
“…As expected, our results confirmed that intracerebral glioblastoma-bearing mice receiving Nox4 knockdown result in an improved overall therapeutic efficiency in radiotherapy. Although we did not investigate the effect of this therapeutic approach on normal tissues, recent studies highlight that radiation induces chronic oxidative stress in rat brain microvascular endothelial cells [44], murine hematopoietic stem cells [45], and human lung fibroblast cells [46], at least in part via up-regulation of Nox4 that leads to the induction of brain and bone marrow injury or fibrosis. Therefore, treatment via Nox4 inhibition may be a good clinical practice to block cycling hypoxia-mediated tumor radioresistance and prevent radiation-induced normal tissue injury in the radiotherapy of GBM.…”
Section: Discussionmentioning
confidence: 95%
“…4 been associated with the expression and activity of NADPH oxidase (Pedruzzi, E. et al 2004;Anrather, J. et al 2006;Manea, A. et al 2008;Manea, A. et al 2010;Park, S. et al 2010). …”
Section: Accepted Manuscriptmentioning
confidence: 96%
“…However, the molecular signalling pathways activated by glycated albumin leading to these effects are still unclear, although some hypotheses can be suggested based on previous data: indeed, transcription factors like NF-κB and AP-1, which are the final step of signalling pathways mediated by kinases like MEK 1/2 and PI3K (Higai, K. et al 2006;Manea, A. et al 2008; Manea, A. et al 2010;Park, S. et al 2010). Moreover, these pathways have also A C C E P T E D M A N U S C R I P T…”
Section: Introductionmentioning
confidence: 97%